Nickel-based anti-carbon-deposition catalyst for ethane dry reforming and preparation and application of nickel-based anti-carbon-deposition catalyst

By using a nickel-based anti-carbon deposit catalyst with a cerium-zirconium composite oxide support and a nickel-based active metal component, the problem of carbon deposit deactivation of the ethane dry reforming catalyst under high temperature and high pressure conditions is solved, and the stability of the catalyst is improved. Selectivity reduces environmental impact and preparation costs, and is suitable for large-scale production.

CN119140097APending Publication Date: 2024-12-17GAOLU AIR PROD & CHEM (SHANGHAI) ENERGY TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411197702.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing ethane dry reforming catalysts have carbon deactivation problems under high temperature and high pressure conditions, resulting in poor stability of the catalyst and difficult to achieve long-term stable operation. At the same time, the chromium-based catalysts are highly toxic, unfriendly in the environment, and the preparation process is complex and cost-effective. high.

Method used

Using cerium-zirconium composite oxide as a support, combining a combined active metal component of nickel and other transition metal elements, a nickel-based anti-carbon deposit catalyst was prepared by hydrothermal method, and reduced under a hydrogen atmosphere for dry reforming of ethane. Reaction improves the catalyst's anti-carbon deposit properties and selectivity.

Benefits of technology

It achieves the efficiency, selectivity and stability of the catalyst, reduces environmental impact and preparation costs, is suitable for large-scale production, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140097A_ABST
    Figure CN119140097A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalyst preparation, and particularly relates to a nickel-based anti-carbon-deposition catalyst for ethane dry reforming and a preparation method and application thereof.The nickel-based anti-carbon-deposition catalyst comprises a carrier and an active metal component loaded on the carrier, the carrier is cerium-zirconium composite oxide, and the active metal component is nickel-zirconium composite oxide. The active metal component is a combination of nickel and transition metal elements. The cerium-zirconium oxide carrier adopted by the invention has rich oxygen vacancies, can improve the reactant gas capture and carbon deposition resistance of the catalyst, and can improve the mechanical strength of the catalyst at the same time. The method is simple in process, free of pollution and capable of being produced and used on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a nickel-based anti-carbon deposition catalyst for ethane dry reforming and its preparation and application. Background Art

[0002] Using carbon dioxide as a weak oxidant, ethane (about 10% of the total content), the second most abundant component in shale gas, can be converted into synthesis gas (H2+CO) through ethane dry reforming technology. Synthesis gas is an important chemical raw material, usually produced by steam reforming or partial oxidation of natural gas, liquefied gas, naphtha, etc., or obtained through highly endothermic and high energy consumption routes such as methane dry reforming (DRM). In comparison, the reaction temperature of ethane dry reforming is lower (more than 100°C lower than that of methane dry reforming), and it can produce synthesis gas under milder reaction conditions and significantly inhibit catalyst deactivation, which has a good application prospect.

[0003] Ethane dry reforming is a key chemical process designed to convert ethane (C2H6), the main component of natural gas, into high-value chemicals and fuels. Ethane is a hydrocarbon that is abundant and widely present in natural gas and liquefied petroleum gas (LPG). However, due to its relatively low carbon number and chemical inertness, direct utilization of ethane resources is a technical challenge. Dry reforming is a very promising solution that can convert ethane into more valuable synthesis gas, which can be further used in Fischer-Tropsch synthesis or in the production of synthetic ammonia, oxo alcohols, methanol and other high-value chemicals.

[0004] The catalyst systems currently used in ethane dry reforming reactions mainly include trimetallic perovskites, supported Pt-based bimetallic catalysts, and supported Ni-based composite catalysts. When cerium dioxide (CeO2) is used as a catalyst support, due to the large number of oxygen vacancies on its surface, it exhibits a stronger metal-support strong interaction, which not only improves the dispersion of Ni species on the catalyst surface, but also enhances the bonding ability between Ni and the CeO2 support. Liu et al. (Angew Chem Int Ed Engl 2016; 55(26): 7455-9.) reported a strong metal-support interaction between nickel nanoparticles and partially reduced CeO2 supports. CO2 was adsorbed and dissociated at oxygen vacancies to generate CO and active oxygen. The synergistic effect of Ni and active oxygen reduced the activation barrier of the CH bond of methane, generating CH on the surface of Ni / CeO2 catalyst. x (x=2,3) species, which lowered the dissociation temperature of methane to 700K. Lustemberg et al. (ACS Catal 2016; 6(12):8184-91.) further proved that Ce 3+The important role of CeO2 in the dissociation of C—H bonds. Smaller Ni particles on CeO2 carriers will experience greater electronic perturbations, which reduces the activation barrier for the first C—H bond breakage. Xie et al. (Appl Catal B Environ 2019; 245: 376-88.) studied the effect of carrier reducibility on the ethane dry reforming reaction in Pt-Ni bimetallic catalysts supported by oxide carriers, and found that the reducible CeO2 carrier can effectively activate CO2 and promote the dissociation of ethane through the bifunctional Mars-van Krevelen redox mechanism, which significantly improves the dry reforming performance of PtNi / CeO2 catalysts. The catalyst-related patents for ethane dry reforming reactions mainly include Fudan University's silicalite-1 zeolite-supported chromium catalyst (CN106563489A) and Sinopec Beijing Research Institute of Chemical Industry's porous chromium trioxide catalyst (CN107175100A). Chromium-based catalysts are highly toxic and environmentally unfriendly, so the development of non-chromium-based dry reforming catalysts has good application prospects. The Shanghai Research Institute of Petrochemicals of Sinopec Corporation has disclosed a nickel-based catalyst with cerium oxide composite oxide as a carrier (CN 112237917 A), but its preparation process requires the use of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock polymers, polyethylene glycol, polypropylene glycol and other surfactants, and the preparation process is complicated and costly. The Shanghai Research Institute of Petrochemicals of Sinopec Corporation has also disclosed an ethane dry reforming catalyst composed of iron and transition metals (CN 115999580 A), but the reaction stability of the catalyst has not been disclosed. Overall, carbon deposition and deactivation are still the main challenges for ethane dry reforming catalysts to achieve long-term stable operation, and the use of effective technical means to achieve effective dissociation and desorption of ethane molecules is the key to designing new ethane dry reforming catalysts.

[0005] In addition, ethane dry reforming reaction has potential significance in environmental protection. Carbon dioxide (CO2) emissions are one of the main drivers of climate change and global warming, so reducing CO2 emissions has become a common goal of the international community. The ethane dry reforming process can provide a way to utilize CO2 and ethane together, reduce CO2 emissions, and convert it into high value-added products. Therefore, finding new, efficient ethane dry reforming catalysts with anti-carbon deposition properties, as well as preparation methods that provide more stable performance, is one of the current research focuses. Summary of the invention

[0006] In view of the shortcomings of the prior art mentioned above, the object of the present invention is to provide a nickel-based anti-carbon deposition catalyst for ethane dry reforming and its preparation and application, so as to solve the limitations of traditional ethane dry reforming catalysts and achieve a more efficient, more selective and more sustainable ethane dry reforming process, thereby meeting energy demand, reducing environmental impact and reducing carbon emissions.

[0007] To achieve the above-mentioned purpose and other related purposes, the present invention provides a nickel-based anti-carbon deposition catalyst for ethane dry reforming, wherein the nickel-based anti-carbon deposition catalyst comprises a carrier and an active metal component loaded on the carrier, wherein the carrier is a cerium-zirconium composite oxide, and the active metal component element is a combination of nickel and other transition metal elements.

[0008] The present invention also provides a method for preparing the nickel-based anti-carbon deposition catalyst for ethane dry reforming as described above, comprising the following steps:

[0009] 1) preparing a cerium-zirconium composite oxide support by a hydrothermal method using a precursor of a cerium component and a precursor of a zirconium component;

[0010] 2) An equal volume of the cerium-zirconium composite oxide carrier is impregnated in a salt solution of an active metal component, and then dried and calcined to obtain a nickel-based anti-carbon deposition catalyst for ethane dry reforming.

[0011] The present invention also provides use of the nickel-based anti-carbon deposition catalyst for ethane dry reforming as described above in an ethane dry reforming reaction.

[0012] The present invention also provides an ethane dry reforming reaction, comprising: reducing the nickel-based anti-carbon deposition catalyst for ethane dry reforming as described above in a hydrogen atmosphere, and then operating the raw gas ethane and carbon dioxide under the catalytic action of the reduced catalyst at a temperature of 550-950° C. and a pressure of 1-5 bar for 100-600 hours.

[0013] As described above, the nickel-based anti-carbon deposition catalyst for ethane dry reforming of the present invention and its preparation and application have the following beneficial effects:

[0014] The nickel-based anti-carbon deposition catalyst for ethane dry reforming of the present invention uses cerium-zirconium composite oxide as a carrier, and attaches active metal components to the carrier. The cerium-zirconium composite oxide has a high content of oxygen vacancies and high mechanical properties. The oxygen vacancies on the carrier can break CC bonds with high selectivity. The active metal components enhance the selectivity of the catalyst in the dry reforming direction, and the highly dispersed active components on the carrier enhance the anti-carbon deposition ability of the catalyst.

[0015] The preparation method of the nickel-based anti-carbon deposition catalyst for ethane dry reforming of the present invention is simple, environmentally friendly and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope image of the nickel-based anti-carbon deposition catalyst for ethane dry reforming obtained in Example 1 of the present invention.

[0017] Figure 2 The ethane dry reforming reaction performance (a) and the anti-carbon deposition performance characterization after the reaction (b) of the nickel-based anti-carbon deposition catalyst for ethane dry reforming obtained in Example 1 of the present invention.

[0018] Figure 3 The ethane dry reforming reaction performance (a) and the anti-carbon deposition performance characterization after the reaction (b) of the nickel-based anti-carbon deposition catalyst for ethane dry reforming obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0019] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0020] Please refer to the attached drawings. In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these two explicitly mentioned devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0021] A first aspect of the present invention provides a nickel-based anti-carbon deposition catalyst for ethane dry reforming, wherein the nickel-based anti-carbon deposition catalyst comprises a carrier and an active metal component loaded on the carrier, wherein the carrier is a cerium-zirconium composite oxide, and the active metal component is selected from a combination of nickel and other transition metal elements.

[0022] In the nickel-based anti-carbon deposition catalyst of the present invention, the content of the carrier is 90-99.9% by weight of the catalyst. For example, 90-91%, 91-92%, 92-93%, 93-94%, 94-95%, 95-96%, 96-97%, 97-98%, 98-99%, 99-99.5%, 99.5-99.7% or 99.7-99.9%. The content of the active component is 0.1%-10% by weight of the oxide. For example, 0.1%-0.3%, 0.3%-0.5%, 0.5%-1%, 1%-2%, 2%-3%, 3%-4%, 4%-5%, 5%-6%, 6%-7%, 7%-8%, 8%-9% or 9%-10%. Within this loading range, the active metal components can be well loaded on the cerium-zirconium composite oxide support.

[0023] In the nickel-based anti-carbon deposition catalyst of the present invention, the molar ratio of cerium element to zirconium element in the cerium-zirconium composite oxide is 1:0.05-1. For example, 1:0.05-0.1, 1:0.1-0.15, 1:0.15-0.2, 1:0.2-0.25, 1:0.25-0.3, 1:0.3-0.4, 1:0.4-0.5, 1:0.5-0.6, 1:0.6-0.7, 1:0.7-0.8, 1:0.8-0.9 or 1:0.9-1. In a preferred embodiment of the present invention, the molar ratio of cerium element to zirconium element in the cerium-zirconium composite oxide is 1:0.1-0.3.

[0024] In the nickel-based anti-carbon deposition catalyst of the present invention, the active metal component is a combination of one or more other transition metal elements and nickel. The molar ratio of the nickel element to the transition metal element is 1:0.05-1. For example, 1:0.05-0.1, 1:0.1-0.15, 1:0.15-0.2, 1:0.2-0.25, 1:0.25-0.3, 1:0.3-0.35, 1:0.35-0.4, 1:0.4-0.45, 1:0.45-0.5, 1:0.5-0.6, 1:0.6-0.7, 1:0.7-0.8, 1:0.8-0.9 or 1:0.9-1. In a preferred embodiment of the present invention, the molar ratio of the nickel element to the transition metal element is 1:0.1-0.5. The one or more other transition metal elements refers to any one of the selected other transition metal elements having a molar percentage in the other transition metal elements in the range of 20 to 100%.

[0025] Wherein, the other transition metal elements are selected from one or more combinations of iron, cobalt, platinum, copper and neodymium. In a preferred embodiment of the present invention, the other transition metal elements are selected from one or more combinations of iron, platinum and neodymium.

[0026] A second aspect of the present invention provides a method for preparing the nickel-based anti-carbon deposition catalyst for ethane dry reforming as described above, comprising the following steps:

[0027] 1) preparing a cerium-zirconium composite oxide support by a hydrothermal method using a precursor of a cerium component and a precursor of a zirconium component;

[0028] 2) An equal volume of the cerium-zirconium composite oxide carrier is impregnated in a salt solution of an active metal component, and then dried and calcined to obtain a nickel-based anti-carbon deposition catalyst for ethane dry reforming.

[0029] In the preparation method of the present invention, the hydrothermal method described in step 1) includes the steps of: dissolving the precursor of the cerium component and the precursor of the zirconium component in a solvent, ultrasonically stirring until the precursors are completely dissolved to obtain a clear solution, performing a hydrothermal reaction, washing, centrifugal separation, drying, and calcining to obtain a cerium-zirconium composite oxide carrier.

[0030] The precursor of the cerium component is selected from one or more of an inorganic salt of cerium and an organic salt of cerium. The inorganic salt of cerium is selected from one or more of cerium nitrate, cerium sulfate, cerous sulfate, and ammonium cerium nitrate. The organic salt of cerium is selected from one or more of cerium acetate, cerium oxalate, and cerium isopropoxide.

[0031] The precursor of the zirconium component is selected from one or more of an inorganic zirconium salt and an organic zirconium salt. The inorganic zirconium salt is selected from one or more of zirconium nitrate and zirconium sulfate. The organic zirconium salt is selected from one or more of zirconium acetate, zirconium propionate, zirconium n-propoxide, and zirconium acetylacetonate.

[0032] The solvent is selected from at least one of deionized water, methanol, ethanol, ethylene glycol, n-propanol, and isopropanol. In a preferred embodiment of the present invention, the solvent is selected from one or more of deionized water, ethanol, and ethylene glycol. The volume percentage of any solvent is in the range of 20 to 100%.

[0033] The temperature of the hydrothermal reaction is 80-200° C. For example, 80-90° C., 90-100° C., 100-110° C., 110-120° C., 120-130° C., 130-140° C., 140-150° C., 150-160° C., 160-170° C., 170-180° C., 180-190° C. or 190-200° C. In a preferred embodiment of the present invention, the temperature of the hydrothermal reaction is 120-160° C.

[0034] The hydrothermal reaction time is 4 to 24 hours. For example, 4 to 6 hours, 6 to 8 hours, 8 to 10 hours, 10 to 12 hours, 12 to 14 hours, 14 to 16 hours, 16 to 18 hours, 18 to 20 hours, 20 to 22 hours or 22 to 24 hours. In a preferred embodiment of the present invention, the hydrothermal reaction time is 6 to 18 hours.

[0035] The washing is performed with deionized water and / or anhydrous ethanol for 3 to 5 times.

[0036] The centrifugal speed is 6000-15000 rpm. For example, it is 6000-7000 rpm, 7000-8000 rpm, 8000-9000 rpm, 9000-10000 rpm, 10000-11000 rpm, 11000-12000 rpm, 12000-13000 rpm, 13000-14000 rpm or 14000-15000 rpm. In a preferred embodiment of the present invention, the centrifugal speed is 8000-12000 rpm.

[0037] The centrifugation time is 5 to 15 min. For example, 5 to 6 min, 6 to 7 min, 7 to 8 min, 8 to 9 min, 9 to 10 min, 10 to 11 min, 11 to 12 min, 12 to 13 min, 13 to 14 min or 14 to 15 min. In a preferred embodiment of the present invention, the centrifugation time is 8 to 12 min.

[0038] The drying temperature is 40-100°C. For example, 40-50°C, 50-60°C, 60-70°C, 70-80°C, 80-90°C or 90-100°C. In a preferred embodiment of the present invention, the drying temperature is 70-100°C. The drying is carried out in a static or fluidized atmosphere; the static or fluidized atmosphere refers to one of dry air, hydrogen, nitrogen or argon.

[0039] The drying time is 10 to 48 hours. For example, it is 10 to 12 hours, 12 to 14 hours, 14 to 16 hours, 16 to 18 hours, 18 to 20 hours, 20 to 24 hours, 24 to 28 hours, 28 to 30 hours, 30 to 34 hours, 34 to 38 hours, 38 to 40 hours, 40 to 44 hours or 44 to 48 hours. In a preferred embodiment of the present invention, the drying time is 12 to 24 hours.

[0040] The calcination temperature is 400-1200°C. For example, 400-500°C, 500-600°C, 600-700°C, 700-800°C, 800-900°C, 900-1000°C, 1000-1100°C or 1100-1200°C. In a preferred embodiment of the present invention, the calcination temperature is 500-800°C. The calcination is carried out in a static or fluidized atmosphere; the static or fluidized atmosphere refers to one of dry air, hydrogen, nitrogen or argon.

[0041] The calcination time is 2 to 12 hours, for example, 2 to 3 hours, 3 to 4 hours, 4 to 5 hours, 5 to 6 hours, 6 to 7 hours, 7 to 8 hours, 8 to 9 hours, 9 to 10 hours, 10 to 11 hours or 11 to 12 hours. In a preferred embodiment of the present invention, the calcination time is 4 to 8 hours.

[0042] In the preparation method of the present invention, the salt solution of the active metal component in step 2) includes a nickel salt solution and a salt solution of a transition metal element.

[0043] Wherein, the nickel salt is selected from one or more of nickel nitrate, nickel acetate, nickel sulfate and nickel chloride.

[0044] The salt of the transition metal element is selected from one or more of ferric nitrate, ferrous sulfate, ferric chloride, ferrous chloride, cobalt nitrate, cobalt acetate, chloroplatinic acid, copper nitrate, copper sulfate, copper chloride, and neodymium nitrate.

[0045] The solvent of the salt solution is one or more of deionized water, ethanol, acetone and dimethylformamide.

[0046] In the preparation method of the present invention, the drying temperature in step 2) is 60-120°C. For example, it is 60-70°C, 70-80°C, 80-90°C, 90-100°C, 100-110°C or 110-120°C. In a preferred embodiment of the present invention, the drying temperature in step 2) is 80-110°C. The drying is carried out in a static or fluidized atmosphere; the static or fluidized atmosphere refers to one of dry air, hydrogen, nitrogen or argon.

[0047] In the preparation method of the present invention, the drying time in step 2) is 2 to 6 hours. For example, 2 to 3 hours, 3 to 4 hours, 4 to 5 hours or 5 to 6 hours. In a preferred embodiment of the present invention, the drying time in step 2) is 4 to 5 hours.

[0048] In the preparation method of the present invention, the calcination temperature in step 2) is 400-1200°C. For example, 400-500°C, 500-600°C, 600-700°C, 700-800°C, 800-900°C, 900-1000°C, 1000-1100°C or 1100-1200°C. In a preferred embodiment of the present invention, the calcination temperature in step 2) is 500-800°C. The calcination is carried out in a static or fluidized atmosphere; the static or fluidized atmosphere refers to one of dry air, hydrogen, nitrogen or argon.

[0049] In the preparation method of the present invention, the calcination time in step 2) is 2 to 12 hours. 2 to 3 hours, 3 to 4 hours, 4 to 5 hours, 5 to 6 hours, 6 to 7 hours, 7 to 8 hours, 8 to 9 hours, 9 to 10 hours, 10 to 11 hours or 11 to 12 hours. In a preferred embodiment of the present invention, the calcination time in step 2) is 4 to 8 hours.

[0050] A third aspect of the present invention provides a use of the nickel-based anti-carbon deposition catalyst as described above in an ethane dry reforming reaction.

[0051] The fourth aspect of the present invention provides an ethane dry reforming reaction, comprising: reducing the nickel-based anti-carbon deposition catalyst as described above in a hydrogen atmosphere, and then catalyzing the raw gas ethane and carbon dioxide under the catalytic action of the reduced catalyst at a temperature of 550-950°C, 550-600°C, 600-650°C, 650-700°C, 700-750°C, 750-800°C, 800-850°C, 850-900°C or 900-950°C and a pressure of 0.1-5 bar, 0.1-0.5 bar, 0.5-1 bar, 1-2 bar, 2-3 bar, 3-4 bar or The reaction mixture is operated at 4 to 5 bar for 100 to 600 h, 100 to 150 h, 150 to 200 h, 200 to 250 h, 250 to 300 h, 300 to 350 h, 350 to 400 h, 400 to 450 h, 450 to 500 h, 500 to 550 h or 550 to 600 h; wherein the reaction volume space velocity is 30,000 to 120,000 ml / g·h, 30,000 to 50,000 ml / g·h, 50,000 to 80,000 ml / g·h, 80,000 to 100,000 ml / g·h or 100,000 to 120,000 ml / g·h.

[0052] Wherein, the reduction is carried out under a hydrogen atmosphere. The reduction temperature is 700-750°C, 700-710°C, 710-720°C, 720-730°C, 730-740°C or 740-750°C; the reduction time is 2-6h, 2-3h, 3-4h, 4-5h or 5-6h. The volume flow rate of the hydrogen is 20-40mL / min, 20-25mL / min, 25-30mL / min, 30-35mL / min or 35-40mL / min.

[0053] The raw gas also includes nitrogen, and the molar ratio of ethane, carbon dioxide and nitrogen is 0.5-0.7:1:2-4, for example, 0.5-0.6:1:2-4, 0.6-0.7:1:2-4, 0.5-0.7:1:2-3 or 0.5-0.7:1:3-4.

[0054] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0055] Example 1

[0056] 5mmol cerium nitrate and 0.5mmol zirconium nitrate were dissolved in 100ml ethanol and deionized water (volume ratio 1:1), the solution was stirred for 30min, and ultrasonic treatment was performed for 30min. The solution was transferred into a 100ml stainless steel hydrothermal reactor, reacted at 180℃ for 18h, the reaction product was centrifuged at 12000rpm for 10min, and washed with deionized water and ethanol for 3 times each. The precipitate was then dried at 100℃ in a static air atmosphere for 24h to obtain precursor A. After drying, precursor A was calcined at 700℃ in a static air atmosphere for 6h to obtain a cerium zirconium oxide carrier; 0.5mmol nickel nitrate hexahydrate and 0.2mmol iron nitrate nonahydrate were weighed and added to 10ml deionized water to prepare a metal salt solution. The metal salt solution was slowly dripped into 5g cerium zirconium oxide carrier by equal volume impregnation method, stirred thoroughly, and dried at 100℃ in a static air atmosphere for 4h to obtain precursor B. The precursor B was placed in a muffle furnace, heated to 750°C and kept constant at that temperature for 4 hours in a static air atmosphere to obtain a catalyst for ethane dry reforming.

[0057] The scanning electron microscopy image of the obtained catalyst is shown in the attached Figure 1 As shown in the attached Figure 1 It can be seen that the microscopic morphology of the catalyst prepared in this example is nano-spherical.

[0058] The catalytic activity of the above catalyst was tested: 150 mg of the catalyst was placed in a fixed bed quartz tube reactor for catalyst performance testing. Before the reaction, it was reduced at 750°C and 20 mL / min of H2 atmosphere for 2 h, and then the raw gas was introduced. The raw gas composition was C2H6:CO2:N2=1:2:2 (total flow rate was 200 mL / min). The catalyst reaction temperature was 650°C and the pressure was 3 MPa. After the reaction for 100 h, if Figure 2 As shown in a, the C2H6 and CO2 conversion rates are maintained at 82% and 88% respectively, the CO selectivity is 98%, and the main product is synthesis gas. Figure 2 b It can be seen that the catalyst synthesized in this example has no carbon deposition phenomenon during the reaction process, which indicates that the catalyst has excellent anti-carbon deposition performance.

[0059] Example 2

[0060] 5.0mmol cerium isopropoxide and 5.0mmol zirconium acetate were dissolved in 100ml ethylene glycol and deionized water (volume ratio 1:1), the solution was stirred for 30min, and ultrasonic treatment was performed for 30min. The solution was transferred into a 100ml stainless steel hydrothermal reactor, reacted at 150℃ for 24h, the reaction product was centrifuged at 10000rpm for 10min, and washed with deionized water and ethanol 3 times each. The precipitate was then dried at 110℃ in a flowing air atmosphere for 18h to obtain precursor A. After drying, precursor A was calcined at a temperature of 700℃ in a static nitrogen atmosphere for 6h to obtain a cerium zirconium oxide carrier; 0.5mmol nickel acetate hexahydrate and 0.2mmol ferrous sulfate heptahydrate were weighed and added to 10ml acetone to prepare a metal salt solution. The metal salt solution was slowly dripped into 8g cerium zirconium oxide carrier by equal volume impregnation method, stirred thoroughly, and dried at 100℃ in a flowing air atmosphere for 4h to obtain precursor B. The precursor B was placed in a muffle furnace, heated to 850°C and kept constant in a static nitrogen atmosphere for 4 hours to obtain a catalyst for ethane dry reforming.

[0061] Test the catalytic activity of the above catalyst: 150 mg of the catalyst was placed in a fixed bed quartz tube reactor for a catalyst performance test. Before the reaction, it was reduced at 700°C and 40 mL / min of H2 atmosphere for 6 h, and then the raw gas was introduced. The raw gas composition was C2H6:CO2:N2=1:2:4 (total flow rate was 200 mL / min). The catalyst reaction temperature was 600°C and the pressure was 1 MPa. After 50 h of reaction, the C2H6 and CO2 conversion rates were maintained at 35% and 37%, respectively, the CO selectivity was 92%, and the main product was synthesis gas.

[0062] Example 3

[0063] Dissolve 5mmol cerium nitrate and 0.5mmol zirconium nitrate in 100ml ethanol and ethylene glycol (volume ratio 1:1), stir the solution thoroughly for 30min, and ultrasonically treat for 30min. Transfer the solution into a 100ml stainless steel hydrothermal reactor, react at 180℃ for 18h, centrifuge the reaction product at 12000rpm for 10min, and wash it with deionized water and ethanol 3 times each. Then dry the precipitate at 100℃ in a static air atmosphere for 24h to obtain precursor A. After drying, calcine precursor A at a temperature of 700℃ in a static air atmosphere for 6h to obtain a cerium zirconium oxide carrier; then weigh 0.5mmol nickel nitrate hexahydrate and 0.4mmol iron nitrate nonahydrate and add 10ml deionized water to prepare a metal salt solution, and use an equal volume impregnation method to slowly drip the metal salt solution into 5g cerium zirconium oxide carrier, stir thoroughly, and dry at 100℃ for 4h to obtain precursor B. The precursor B was placed in a muffle furnace, heated to 750°C and kept constant at that temperature for 4 hours in a static air atmosphere to obtain a catalyst for ethane dry reforming.

[0064] The catalytic activity of the above catalyst was tested: 150 mg of the catalyst was placed in a fixed bed quartz tube reactor for catalyst performance testing. Before the reaction, it was reduced at 750°C and 30 mL / min of H2 atmosphere for 5 h, and then the raw gas was introduced. The raw gas composition was C2H6:CO2:N2=1:2:2 (total flow rate was 150 mL / min). The catalyst reaction temperature was 600°C and the pressure was 1 MPa. After the reaction for 100 h, if Figure 3 As shown in a, the conversion rates of C2H6 and CO2 are maintained at 44% and 55% respectively, the CO selectivity is 95%, and the main product is synthesis gas. Figure 3 b and Figure 2 b. In contrast, the reaction activity of the high Ni / Fe ratio catalyst synthesized in this example is relatively low, and the thermogravimetric results show that the catalyst has obvious carbon deposition.

[0065] Example 4

[0066] Dissolve 10mmol of ammonium cerium nitrate and 2mmol of zirconium nitrate in 100ml of ethanol, stir the solution thoroughly for 30min, and ultrasonically treat for 30min. Transfer the solution into a 100ml stainless steel hydrothermal reactor, react at 150℃ for 24h, centrifuge the reaction product at 10000rpm for 12min, and wash it with deionized water and ethanol 5 times each. Then dry the precipitate in a static air atmosphere at 120℃ for 20h to obtain precursor A. After drying, calcine precursor A in a flowing air atmosphere at 600℃ for 6h to obtain a cerium zirconium oxide carrier; then weigh 1mmol of nickel citrate and 0.8mmol of cobalt nitrate hexahydrate and add 10ml of ethanol to prepare a metal salt solution, and use an equal volume impregnation method to slowly drip the metal salt solution into 10g of the cerium zirconium oxide carrier, stir it thoroughly, and dry it in a flowing air atmosphere at 120℃ for 6h to obtain precursor B. The precursor B was placed in a muffle furnace, heated to 750°C and kept constant at this temperature in a flowing air atmosphere for 6 hours to obtain a catalyst for ethane dry reforming.

[0067] Test the catalytic activity of the above catalyst: 150 mg of the catalyst was placed in a fixed bed quartz tube reactor for a catalyst performance test. Before the reaction, it was reduced at 750°C and 40 mL / min of H2 atmosphere for 4 h, and then the raw gas was introduced. The raw gas composition was C2H6:CO2:N2=1:2:2 (total flow rate was 100 mL / min). The catalyst reaction temperature was 680°C and the pressure was 0.1 MPa. After 100 h of reaction, the C2H6 and CO2 conversion rates were maintained at 50% and 55%, respectively, the CO selectivity was 85.5%, and the main product was synthesis gas.

[0068] Example 5

[0069] 5mmol of cerium sulfate and 0.5mmol of zirconium sulfate were dissolved in 100ml of ethanol and deionized water (volume ratio 1:1), the solution was stirred for 30min, and ultrasonic treatment was performed for 30min. The solution was transferred into a 100ml stainless steel hydrothermal reactor, reacted at 180℃ for 12h, the reaction product was centrifuged at 10000rpm for 10min, and washed with deionized water and ethanol 4 times each. The precipitate was then dried at 110℃ in a static air atmosphere for 16h to obtain precursor A. After drying, precursor A was calcined at 700℃ in a static air atmosphere for 6h to obtain a cerium zirconium oxide carrier; 1mmol of nickel chloride hexahydrate and 0.5mmol of chloroplatinic acid were weighed and added to 10ml of deionized water to prepare a metal salt solution. The metal salt solution was slowly dripped into 5g of the cerium zirconium oxide carrier by an equal volume impregnation method, stirred thoroughly, and dried at 120℃ for 4h to obtain precursor B. The precursor B was placed in a muffle furnace, heated to 650°C and kept constant at this temperature in a flowing air atmosphere for 4 hours to obtain a catalyst for ethane dry reforming.

[0070] Test the catalytic activity of the above catalyst: 150 mg of the catalyst was placed in a fixed bed quartz tube reactor for a catalyst performance test. Before the reaction, it was reduced at 750°C and 20 mL / min of H2 atmosphere for 2 h, and then the raw gas was introduced. The raw gas composition was C2H6:CO2:N2=1:2:4 (total flow rate was 180 mL / min). The catalyst reaction temperature was 700°C and the pressure was 3 MPa. After 100 h of reaction, the C2H6 and CO2 conversion rates were maintained at 72% and 75%, respectively, the CO selectivity was 95%, and the main product was synthesis gas.

[0071] Example 6

[0072] 5.0mmol cerium oxalate and 0.5mmol zirconium propionate were dissolved in 100ml ethanol and deionized water (volume ratio 1:1), the solution was stirred for 30min, and ultrasonic treatment was performed for 30min. The solution was transferred into a 100ml stainless steel hydrothermal reactor, reacted at 200℃ for 15h, the reaction product was centrifuged at 12000rpm for 10min, and washed with deionized water and ethanol for 3 times each. The precipitate was then dried at 100℃ in a flowing argon atmosphere for 24h to obtain precursor A. After drying, precursor A was calcined at 800℃ in a flowing air atmosphere for 6h to obtain a cerium zirconium oxide carrier; 1mmol nickel nitrate hexahydrate and 0.1mmol iron nitrate nonahydrate were weighed and added to 10ml deionized water to prepare a metal salt solution, and the metal salt solution was slowly dripped into the cerium zirconium oxide carrier by an equal volume impregnation method, stirred thoroughly, and dried at 100℃ in a flowing air atmosphere for 4h to obtain precursor B. The precursor B was placed in a muffle furnace, heated to 750°C and kept constant at that temperature for 4 hours in a static air atmosphere to obtain a catalyst for ethane dry reforming.

[0073] Test the catalytic activity of the above catalyst: 150 mg of the catalyst was placed in a fixed bed quartz tube reactor for catalyst performance test. Before the reaction, it was reduced at 750°C and 20 mL / min of H2 atmosphere for 2 h, and then the raw gas was introduced. The raw gas composition was C2H6:CO2:N2=1:2:2 (total flow rate was 150 mL / min). The catalyst reaction temperature was 600°C and the pressure was 1 MPa. After 100 h of reaction, the C2H6 and CO2 conversion rates were maintained at 70% and 75%, respectively, the CO selectivity was 95%, and the main product was synthesis gas.

[0074] In summary, the catalyst for ethane dry reforming of the present invention uses cerium-zirconium composite oxide as a carrier, and the active metal component is attached to the carrier. The cerium-zirconium composite oxide as a carrier has a high content of oxygen vacancies and high mechanical properties. The oxygen vacancies on the carrier can break CC bonds with high selectivity, thereby enhancing the selectivity of the catalyst in the dry reforming direction. That is, the catalyst of the present invention has high activity, high stability, high selectivity, and low price. Therefore, the present invention effectively overcomes various shortcomings in the prior art and has high industrial utilization value.

[0075] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A nickel-based anti-carbon deposition catalyst for ethane dry reforming, characterized in that: The nickel-based anti-carbon deposition catalyst comprises a carrier and an active metal component supported on the carrier. The carrier is a cerium-zirconium composite oxide, and the active metal component element is a combination of nickel and other transition metal elements.

2. The nickel-based anti-carbon deposition catalyst according to claim 1, characterized in that: Calculated as a percentage of catalyst mass, the content of the carrier is 90-99.9%, and the content of the active metal component is 0.1%-10% as an oxide; And / or, in the cerium-zirconium composite oxide, the molar ratio of cerium element to zirconium element is 1:0.05-1; And / or, the active metal component is a combination of one or more other transition metal elements and nickel; And / or, the molar ratio of the nickel element to the other transition metal element is 1:0.05-1; And / or, the other transition metal elements are selected from one or more combinations of iron, cobalt, platinum, copper and neodymium.

3. A method for preparing a nickel-based anti-carbon deposition catalyst for ethane dry reforming according to any one of claims 1 to 2, characterized in that: The following steps are involved: 1) preparing a cerium-zirconium composite oxide support by a hydrothermal method using a precursor of a cerium component and a precursor of a zirconium component; 2) An equal volume of the cerium-zirconium composite oxide carrier is impregnated in a salt solution of an active metal component, and then dried and calcined to obtain a nickel-based anti-carbon deposition catalyst for ethane dry reforming.

4. The preparation method according to claim 3, characterized in that: The hydrothermal method in step 1) includes the steps of: dissolving the precursor of the cerium component and the precursor of the zirconium component in a solvent, ultrasonically stirring until the precursors are completely dissolved to obtain a clear solution, performing a hydrothermal reaction, washing, centrifugal separation, drying, and calcining to obtain a cerium-zirconium composite oxide carrier.

5. The preparation method according to claim 4, characterized in that: The hydrothermal process may also include one or more of the following features: A) the precursor of the cerium component is selected from one or more of an inorganic salt of cerium and an organic salt of cerium; preferably, the inorganic salt of cerium is selected from one or more of cerium nitrate, cerium sulfate, cerous sulfate, and ammonium cerium nitrate; preferably, the organic salt of cerium is selected from one or more of cerium acetate, cerium oxalate, and cerium isopropoxide; B) the precursor of the zirconium component is selected from one or more of zirconium inorganic salts and zirconium organic salts; preferably, the zirconium inorganic salt is selected from one or more of zirconium nitrate and zirconium sulfate; preferably, the zirconium organic salt is selected from one or more of zirconium acetate, zirconium propionate, zirconium n-propoxide and zirconium acetylacetonate; C) the solvent is selected from at least one of deionized water, methanol, ethanol, ethylene glycol, n-propanol, and isopropanol; D) the molar concentration of cerium and zirconium ions in the precursor clear solution is 0.1 to 1000 mmol / L; E) the temperature of the hydrothermal reaction is 80 to 200° C.; F) the hydrothermal reaction time is 4 to 24 hours; G) washing with deionized water and / or anhydrous ethanol for 3 to 5 times; H) the centrifugal speed is 6000-15000 rpm; I) the centrifugation time is 5 to 15 minutes; J) the drying temperature is 40 to 100° C.; K) the drying time is 10 to 48 hours; L) the calcination temperature is 400-1200° C.; M) The calcination time is 2 to 12 hours.

6. The preparation method according to claim 3, characterized in that: The salt solution of the active metal component in step 2) includes a nickel salt solution and a salt solution of other transition metal elements; and / or, the solvent of the salt solution in step 2) is one or more of deionized water, ethanol, acetone, and dimethylformamide; And / or, the drying temperature in step 2) is 60-120°C; And / or, the drying time in step 2) is 2 to 6 hours; And / or, the calcination temperature in step 2) is 400-1200°C; And / or, the calcination time in step 2) is 2 to 12 hours.

7. The preparation method according to claim 6, characterized in that: The nickel salt is selected from one or more of nickel nitrate, nickel sulfate, nickel chloride, nickel acetate, nickel citrate, and nickel acetate; And / or, the salt of the transition metal element is selected from one or more of ferric nitrate, ferrous sulfate, ferric chloride, ferrous chloride, cobalt nitrate, cobalt acetate, chloroplatinic acid, copper nitrate, copper sulfate, copper chloride, and neodymium nitrate.

8. Use of the nickel-based anti-carbon deposition catalyst for ethane dry reforming according to any one of claims 1 to 2 in ethane dry reforming reaction.

9. An ethane dry reforming reaction, characterized in that: include: The nickel-based anti-carbon deposition catalyst for ethane dry reforming as described in any one of claims 1 to 2 is reduced in a hydrogen atmosphere, and then the raw gas ethane and carbon dioxide are operated under the catalytic action of the reduced catalyst at a temperature of 550 to 950° C. and a pressure of 0.1 to 5 MPa for 100 to 600 hours.

10. The ethane dry reforming reaction according to claim 9, characterized in that: The raw gas also contains nitrogen, and the molar ratio of ethane, carbon dioxide and nitrogen is 0.5-0.7:1:2-4.

Citation Information

Cited By

  • Preparation method of monatomic catalyst with adjustable coordination environment

    CN121288825A